The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s13199-009-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Hippophae salicifolia D. Don of temperate and sub-alpine forests of North Sikkim Himalayas—a case study

Abstract: Hippophae salicifolia D. Don or Sea buckthorn is one species that has great potential for improving ecological and economic developments in the mountain areas of North Sikkim. The plant is found naturally at altitudes ranging from 2,377 to 3,093 m. in riverine (river side or torrential side) and non-riverine (non river or non torrential side) areas where geo-physico-chemical parameters like aerial temperature, aerial moisture, soil pH, soil temperature, and soil moisture varied significantly. We analyzed ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…On the basis of the presentday environmental preferences of Juniperus, minimum July temperature may be assessed as exceeding 10°C (Iversen 1954, Isarin et al 1998). These zones were also marked by abundant pollen of Hippophaë rhamnoides shrubs, suggesting mean annual temperatures ranging from 4.7°C to 15.6°C (Basistha et al 2010). High amounts of this pollen in zone WE-1, in the diagrams plotted for WE'08 (2%), WE'10/2 (23%) and WE'10/3 (5%), indicate that the species was widespread in the study area.…”
Section: We-2 Poaceae-betula-hippophaë L Paz;mentioning
confidence: 87%
“…On the basis of the presentday environmental preferences of Juniperus, minimum July temperature may be assessed as exceeding 10°C (Iversen 1954, Isarin et al 1998). These zones were also marked by abundant pollen of Hippophaë rhamnoides shrubs, suggesting mean annual temperatures ranging from 4.7°C to 15.6°C (Basistha et al 2010). High amounts of this pollen in zone WE-1, in the diagrams plotted for WE'08 (2%), WE'10/2 (23%) and WE'10/3 (5%), indicate that the species was widespread in the study area.…”
Section: We-2 Poaceae-betula-hippophaë L Paz;mentioning
confidence: 87%
“…and Withania somnifera were selected on the basis of their biological activity. Hydro-alcohol extract of four medicinal plants(Nyctanthe sarbortristis; Hippophae salcifolia ;Ocimum tenuiflorum ; Withania somnifera) has been reported to possess potent different activityanti-inflammatory,anti-oxidant,COX-2 inhibitor and analgesic effect and chronic fatigue, nervous exhaustion, memory loss, neurodegenerative disorders etc, respectively due to presence of major effective constituents such as nyctanthic, lupeol, ascorbic acid, flavonoids, folic acid, oleanolic acid, ursolic acid, rosmarinic eugenol and 35 withanolides with 12 alkaloids and several sitoindosides [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Therefore, all the four plants have shown their action on various targets involved with depression like monoamine content, proinflammatory markers, behavioral pattern etc and the selected four plants were taken and after determination of bio-activity the plants were taken for standardization and quality control studies and to develop a polyherbal formulation beneficial in the management of depression of varying etiology.…”
Section: Lipid Peroxidation and Glutathionementioning
confidence: 99%
“…Nyctanthe sarbor-tristis, (N. arbor-tristis,) (Family Oleaceae) is an herb that has been used in India for centuries as an anti-inflammatory [16], analgesic, antipyretic, ulcerogenic activities [17][18][19][20], immunostimulant activity and anxiolytic activity. Hippophae salcifolia (H. salcifolia) (Seabuckthorn) are deciduous shrubs in the family Elaeagnaceae that traditionally used as anti-stress and improve, enhance physical endurance, mental function alone but there are limited published data in related to centrals nervous system disorders [19][20][21]. It has also shown anti-oxidant, immuno-modulatory, antiinflammatory and homocysteine lowering effects because it is a rich source of flavonoids, vitamins, proteins, amino acids, folic acid, phytosterol, alpha-tocopherol and phenolic compounds [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These plants have the ability to fix atmospheric nitrogen (N 2 ) by the formation of root nodules with N 2 -fixing actinomycetes genus Frankia. It has already been reported that the actinorhizal plants like Alnus, Hippophae, Casuarina, Elaeagnus and Myrica fix atmospheric nitrogen and increase the soil fertility of the surrounding area (Palmgren et al 1985;Basistha et al 2010;Andrade et al 2015;Sen et al 2008;Khamzina et al 2009;Permar and Fisher 1983). Besides fixing atmospheric nitrogen (N 2 ), many actinorhizal plants are known to serve as functional fruits and may have medicinal values.…”
Section: Introductionmentioning
confidence: 99%